Supporting Change in Literacy Instruction in Malawi. Issue 2 (3rd February 2014) - Sailors, Misty; Hoffman, James V.; David Pearson, P.; McClung, Nicola; Shin, Jaran; Phiri, Liveness Mwale; Saka, Tionge
Abstract In this study, we examined the effectiveness of an innovative approach to literacy instruction in Malawi on teachers' perceptions, attitudes, and instructional practices. Two groups participated in the study: Treatment teachers received complementary teaching and learning materials, workshops, and directive coaching, and control teachers received no intervention. After this five‐month intervention, treatment teachers were significantly more comfortable with their languages of instruction and were more positive about their teaching ability, beliefs about the learning materials in their classroom, and beliefs about the culture of reading in their communities than control teachers were. There were no significant differences between groups when we analyzed their teaching practices or the engagement of their students. The coaching model proved to be associated with changes in teachers' beliefs and perceptions on many of our variables. These findings suggest that the program under examination was successful in promoting the conditions for success (teacher beliefs and perceptions). Further, the findings suggest that the implementation of coaching was an important source of support in implementing changes.